(untitled) (European Journal of Transport and Infrastructure Research, 2009)
Editorial Board EJTIR Bert van Wee (Editor in Chief) Delft University of Technology Caspar Chorus (Co-Editor in Chief) Delft University of Technology Vincent Marchau (Secretary) Delft University of Technology Serge Hoogendoorn Delft University of Technology Dominic Stead Delft University of Technology Lóri Tavasszy Radboud University Nijmegen Rob van der Heijden Radboud University Nijmegen Eddy van de Voorde University of Antwerp Advisory Board EJTIR Peter Nijkamp (Chairman) The Netherlands Stef Weijers The Netherlands Erik Verhoef The Netherlands Daniel Schefer Israel Frank Sanders The Netherlands Piet Rietveld The Netherlands Aura Regiani Italy Robert Paaswell United States of America Ricco Maggi Switzerland Martin Lanzendorf The Netherlands Veli Himanen Finland Ingo Hansen The Netherlands Marina van Geenhuizen The Netherlands Piet Bovy The Netherlands Michel Beuthe Belgium David Banister United Kingdom